2017
DOI: 10.1021/acs.jpca.7b03454
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insights on Solvent Control of Intramolecular and Intermolecular Proton Transfer of 2-(2′-Hydroxyphenyl)benzimidazole

Abstract: Excited-state proton transfer (ESPT) processes of 2-(2'-hydroxyphenyl)benzimidazole (HBI) and its complexation with protic solvents (HO, CHOH, and NH) have been investigated by both static calculations and dynamics simulations using density functional theory (DFT) at B3LYP/TZVP theoretical level for ground state (S) and time-dependent (TD)-DFT at TD-B3LYP/TZVP for excited state (S). For static calculations, absorption and emission spectra, infrared (IR) vibrational spectra of O-H mode, frontier molecular orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…In the work of Ramalho et al 19 , some functionals were tested and B3LYP was the most adequate functional employed in the study of an amino-naphthoquinone derivative capable of performing ESIPT. Also, previous studies demonstrated that the functional B3LYP is very reliable for obtaining the potential energy curves in the ground and excited states (see, for example, references 4,19,49,50,24,27,[43][44][45][46][47][48].…”
Section: Methodsmentioning
confidence: 99%
“…In the work of Ramalho et al 19 , some functionals were tested and B3LYP was the most adequate functional employed in the study of an amino-naphthoquinone derivative capable of performing ESIPT. Also, previous studies demonstrated that the functional B3LYP is very reliable for obtaining the potential energy curves in the ground and excited states (see, for example, references 4,19,49,50,24,27,[43][44][45][46][47][48].…”
Section: Methodsmentioning
confidence: 99%
“…From the method of choice, among seven tested functionals, the most suitable method for reproducing the enol absorption spectra of all molecules is the B3LYP because this method provides the most satisfactory agreement with the experimental data. Moreover, previous studies have been proven that the B3LYP and TD-B3LYP functionals with TZVP basis set are suitable to describe electronic and photophysical properties as well as the PT process of ESIPT molecules [29,[57][58][59][60][61][62]. Therefore, the B3LYP was further em ployed to optimize the enol form in the S 1 state and the keto form both in S 0 and the S 1 states of all molecules.…”
Section: Static Calculationsmentioning
confidence: 99%
“…Solving Newton's equation of nuclear motion was achieved by the Velocity-Verlet algorithm [22]. The Born-Oppenheimer energies and gradients were obtained at each time step by mean of the TD-B3LYP method, which has been tested and used in dynamic simulations in previous studies [60][61][62][66][67][68]75]. All trajectories for each complex were simulated with a time step of 1 fs with the maximal duration of 500 fs, which is long enough to cover the pre-and post-PT regimes.…”
Section: Dynamics Simulationsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25] As far as we know, one of the most challenging cases in photochemical field is the investigation of excited-state hydrogen bonding interactions in molecules due to both proton acceptor and donor moieties. [26][27][28][29][30] Accordingly, excited-state dynamical processes of hydrogen bonding molecules should be usually complicated by the fact that multiple equilibriums and various species can appear in excited states. In general, the individual or simultaneous ESIPT reaction suffered by these centers might give rise to the observation of different exciplexes of photo-tautomers, respectively.…”
Section: Introductionmentioning
confidence: 99%